2020
DOI: 10.1136/bmjopen-2019-035595
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal BCG vaccination and child survival in TB-exposed and TB-unexposed children: a prospective cohort study

Abstract: ObjectivesTo assess the association between neonatal BCG vaccination and mortality between 28 days and 3 years of age among tuberculosis (TB)-exposed and TB-unexposed children.DesignProspective cohort study.SettingBandim Health Project runs an urban Health and Demographic Surveillance site in Guinea-Bissau with registration of mortality, vaccination status and TB cases.ParticipantsChildren entered the analysis when their vaccination card was inspected after 28 days of age and remained under surveillance to 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Most of the effect could not be explained by reduction of tuberculosis (TB), against which the vaccine was intended. This finding has been confirmed in several recent international studies [21–23], and other live vaccines such as measles and yellow fever vaccines have been demonstrated to have similar effects [24]. This heterologous immunity induced through BCG can be viewed as targeted priming of immunological responses, so that a second microbial challenge will result in a more powerful and tailored counterstrike by the immune system [10, 11, 25].…”
Section: Covid‐19 Bcg and Trained Immunitymentioning
confidence: 63%
“…Most of the effect could not be explained by reduction of tuberculosis (TB), against which the vaccine was intended. This finding has been confirmed in several recent international studies [21–23], and other live vaccines such as measles and yellow fever vaccines have been demonstrated to have similar effects [24]. This heterologous immunity induced through BCG can be viewed as targeted priming of immunological responses, so that a second microbial challenge will result in a more powerful and tailored counterstrike by the immune system [10, 11, 25].…”
Section: Covid‐19 Bcg and Trained Immunitymentioning
confidence: 63%
“…In addition, increasing evidence suggests BCG vaccine has non-specific effects on child survival, protecting vaccinated children from infections beyond tuberculosis (TB). 26 Our study did not attempt to clarify to what extent vaccinated children had a reduced mortality from TB or other causes. But based on existing evidence and a very small proportion of under-5 deaths from TB in Uganda, it is likely that those who received BCG vaccine were protected against non-TB infectious diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Neonatal BCG vaccination has been shown to be associated with lower mortality rates among both TB-exposed and TB-unexposed children. 12 Three randomized controlled trials of early BCG vaccination in Guinea-Bissau found a 38% reduction in all-cause neonatal mortality. 13 These effects do not only benefit infants, as a recent clinical trial revealed that revaccinating at-risk teenagers with the BCG vaccine they first got as infants, could significantly reduce the threat of these patients becoming carriers of TB infection.…”
Section: Observations Of Non-specific Effects Of Bcgmentioning
confidence: 99%
“…Numerous studies have investigated whether BCG vaccination reduces TB disease burden and associated mortality. Neonatal BCG vaccination has been shown to be associated with lower mortality rates among both TB-exposed and TB-unexposed children (Thysen et al, 2020). Three randomized controlled trials of early BCG vaccination in Guinea-Bissau found a 38% reduction in all-cause neonatal mortality (Jensen et al, 2020).…”
Section: Observations Of Non-specific Effects Of Bcgmentioning
confidence: 99%